2019
DOI: 10.3389/fpsyg.2019.01389
|View full text |Cite|
|
Sign up to set email alerts
|

How Do We Recognize Emotion From Movement? Specific Motor Components Contribute to the Recognition of Each Emotion

Abstract: Are there movement features that are recognized as expressing each basic emotion by most people, and what are they? In our previous study we identified sets of Laban movement components that, when moved, elicited the basic emotions of anger, sadness, fear, and happiness. Our current study aimed to investigate if movements composed from those sets would be recognized as expressing those emotions, regardless of any instruction to the mover to portray emotion. Our stimuli included 113 video-clips of five Certifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…At present, limited research has been conducted to investigate the effectiveness of these innate patterns of movement to brain function and physiology (Chatfield and Barr, 1994 ). The primary work in this field has focused on the connection between movement patterns, quantified through LMA, and their connection to emotional expression or the expressive quality of movement (Bernardet et al, 2019 ; Melzer et al, 2019 ; Tsachor and Shafir, 2019 ). More recently, LMA in combination with EEG has been used to extract neural signatures linked to expressive human movement (Cruz-Garza et al, 2014 ).…”
Section: The Synchronicity Hypothesis Of Dancementioning
confidence: 99%
See 1 more Smart Citation
“…At present, limited research has been conducted to investigate the effectiveness of these innate patterns of movement to brain function and physiology (Chatfield and Barr, 1994 ). The primary work in this field has focused on the connection between movement patterns, quantified through LMA, and their connection to emotional expression or the expressive quality of movement (Bernardet et al, 2019 ; Melzer et al, 2019 ; Tsachor and Shafir, 2019 ). More recently, LMA in combination with EEG has been used to extract neural signatures linked to expressive human movement (Cruz-Garza et al, 2014 ).…”
Section: The Synchronicity Hypothesis Of Dancementioning
confidence: 99%
“…Dance performance can also elicit intense emotional reactions for dancers and audience members alike. Using Laban Movement Analysis, researchers have shown that specific movement patterns (in the absence of facial expressions) elicit similar emotions (e.g., happiness, sadness, fear, or anger) for both the dancer and observer (Shafir et al, 2013 , 2015 ; Melzer et al, 2019 ). The emotional aspect of dance is thought to be the crucial element regarding the beneficial effects of DMT, and dancers show heightened emotional intelligence over non-dance counterparts (Jeong et al, 2005 ; Punkanen et al, 2017 ; San-Juan-Ferrer and Hípola, 2020 ).…”
Section: The Neurobehavioral Functions Of Dance and Their Connection mentioning
confidence: 99%
“…however, for many other people in the world, interacting with others that have partially occluded faces is more common. For example, prior to the COVID-19 pandemic many Indeed, emotions can be recognized correctly just from particular body movements and contextual body cues [55][56][57]. Vocal cues such as emotional prosody, or "tone of voice", as well as non-verbal expressions of emotions such as a sigh or laugh, likewise carry significant clues to a speaker's internal state [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…TBMA promotes inhibition of old habits, reappraisal of pre-existing assumptions, and possibilities to respond to stress in novel ways offering greater emotional self-regulation. Because emotions and movement are so closely related ( Kirchhoff, 2018 ; Melzer et al, 2019 ), non-verbal behavior, as in expressive movement ( Krantz and Pennebaker, 2007 ) and mark-making practices, can encourage reflections on a range of feelings (sadness, fear, anger, joy) which some people with MUS find difficult to identify and verbalize (alexithymia). This somatic, bottom-up intervention removes the focus on verbal language and memory, working with implicit elements available in the non-verbal.…”
Section: Discussionmentioning
confidence: 99%